Translating caste - Kalitā, Arūpā Paṭaṃgīẏā; Basu, Tapan (Studies in culture and translation, 2002)
Volume comprises eight translated short stories on the theme of caste along with contributed articles on socio-cultural aspects of caste in modern India.